Digital System for Vaccines Management in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
An article about digital System for vaccines management in Thai supply chain aim to present for vaccines management in Thailand for better effective The vaccines management needs need to be injected boost immunity . The processes consisted of Seller, Manufacture , Distribution, Customers and Satisfaction, All component connect with digital technology in the Thailand with the supply chain. This truly added the immunity in Thailand .The supply chain and information system may be appropriately applied in actual work settings.